Pemanfaatan Air Limbah Domestik PT. X Kota Surabaya sebagai Penyiraman Ruang Terbuka Hijau - Adinda Rahmatanti; Yayok Suryo Purnomo (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
PT. X’s activities, such as the consumption of clean water by workers, visitors, and building maintenance produce domestic liquid waste in the form of grey water. Domestic liquid waste originating form PT. X is used for watering the company’s green open space, that has an area of 2384,4 . The water treatment used is anaerobic and aerobic biofilter. The volume of liquid waste grey water is 70 of the liquid waste produced at 4,09/day, sp the water utilization effieciency is 70. The resulting domestic liquid waste contains the pollutant parameters BOD5, COD, TSS, -N, oil grease, and Total Coliform, so processing by WWTP is required to be below quality standards. The processing units used consist of an interceptor tank, equalization tank, initial settling tank, anaerobic, aerobic, sedimentation, and efflluent tank. After processing and fulfil the quality standards, which has been set, the resulting efflulent is used for at a dose of 0,002 m3/m2/day with a watering frequency of 2 times a day.